THE RELATIONSHIP BETWEEN DEPRESSION AND ACADEMIC PROCRASTINATION IN EFL CLASSROOM - Jannatunnura; Sukri Adani (Yayasan Nusantara Hasana Berdikari, 2023)
Depression among students is a common issue that is believed to have a great impact on their academic performance. In the academic environment, depression among students leads to another problem such as procrastination, which causes academic failure. This kind of procrastination is called academic procrastination. The current study aimed to have a deep investigation into the relationship between students’ depression and their academic procrastination. In collecting the data, it applied the quantitative method through the distribution of a questionnaire to 100 students or research subjects. Then the data was analyzed by SPSS. In the analysis, the correlation test was carried out which resulted in r = .356, p = .001. This shows that there is a positive correlation between depression and academic procrastination. Students with high levels of depression have high levels of procrastination.